Investigation of the design, manufacture and testing of additively manufactured coils for electric motor applications - Silbernagel, Cassidy (2019)
Electric motor design has been relatively unchanged for nearly a century. However, there is a movement in our world to replace inefficient combustion technology with electricity. While current electric motor technology is being used in numerous areas, manufacturing has been limited to traditional techniques which result in inefficient and unreliable machines for achieving those electrification goals. As a result, there needs to be a shift in how these motors are manufactured and designed. Additive manufacturing (AM) can provide this shift, however, there has been both a lack of information on how to use AM to design for these applications and of electrical properties for AM materials processed by Laser Powder Bed Fusion (LPBF). This work helps to fill in some of this missing information.